Missing persons and its relation with human sacrifice in witchcraft ritual: a review - Mahyuddin, Ismail; Nurkarimah, Yusof (Universiti Malaysia Pahang, 2019)
The case of missing people especially children in Malaysia is quite alarming. Based on the statistics released by Royal Malaysia Police Headquarter Bukit Aman in 2018, there were 5,721 missing persons cases reported. Only 3,127 people were successfully found. There are many factors associated with this loss such as personal problem, stress, friends’ influence, family break-up and so on. One of the underrated aspects is the practice of black magic by killing and obtaining valuable organs for the purpose of demonic worship. This study specifically seeks to explore the possible connections of missing persons cases, especially the rising missing children cases, with rituals of demonic worship and human sacrifice in witchcraft. This study applies deductive and inductive analyses by focusing on document analysis including cases reported in court. Evidence was found that these practices of detestful black magic require certain organs of a human body, especially of a child, to be one of the devil's objects of worship. This study will also discuss illustration (a) of the section 364 of the Penal Code which is specifically mentioned about crime of kidnapping or abducting any person to be murdered. The results of this study justify a proactive action need to be taken by the authorities to fight against witchcraft.